Pelanggaran Kode Etik oleh Hakim Mahkamah Konstitusi Terkait Dengan Putusan Mahkamah Konstitusi Nomor 90/Puu-Xxi/2023 - Nala Syandhira Suzeeta; Kayus Kayowuan Lewoleba (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Judges who act as executors and spearheads of justice and interact with the public are expected to have high professionalism in considering and making legal decisions in a case. In carrying out their duties, a judge is required to comply with the applicable code of ethics. When a judge violates the professional code of ethics, he will be given sanctions according to the violation he has committed. The case of violating the code of ethics that recently occurred was the case regarding Anwar Usman as Chairman of the Constitutional Court who was proven to have violated the professional code of ethics for judges in relation to Decision Number 90/PUU-XXI/2023. The aim of this research is to find out the accountability of a judge who has violated the professional code of ethics and to know the role of the Honorary Council of the Constitutional Court in handling cases of violations of the code of ethics committed by constitutional judges. This research uses a normative juridical method by referring to legal norms contained in statutory regulations as well as legal norms that exist in society. An approach that refers to applicable laws and regulations including principles, principles and doctrine. Judges who violate the code of ethics can impose three types of sanctions taking into account the background, level of seriousness and consequences of the violation. The Honorary Council of the Constitutional Court is an instrument formed by the Constitutional Court with the aim of maintaining and upholding honor, nobility and dignity. The authority possessed by the Honorary Council of the Constitutional Court includes maintaining the dignity and honor of the Constitutional Court, examining and deciding on allegations of violations of the code of ethics and behavior of constitutional judges. The trial led by Jimly Asshiddiqie as Chair of the Honorary Council of the Constitutional Court (MKMK) through the Decision of the Honorary Council of the Constitutional Court Number 02/MKMK/L/11/2923 stated that Anwar Usman in this case had been proven to have violated the code of professional ethics and behavior of judges. For this reason, Anwar Usman was dismissed from his position as Chairman of the Constitutional Court.